Jealous love and morbid jealousy - Maggini, C.; Lundgren, E.; Leuci, E. (Acta Biomedica Atenei Parmensis, 2006)
Jealous love and morbid jealousy, although inextricably linked, cannot be considered the same: jealous love (trait jealousy) is the behavioral and cognitive-affective precondition of morbid jealousy (state jealousy). Love is jealous when it is devoured by the desire for the exclusive and total possession of the partner, whose unconditional and continued presence is avidly requested. This type of love, in addition, is permeated by the need to know what the other is thinking, in order to scrutinize every minimal flaw in the faithfulness of the partner even in his or her innermost thoughts and fantasies; in it, jealousy is virtually always present, even in the absence of a triggering event, because captative love, by its very nature, includes the expectation of a conflict which inevitably actually takes place in reality. Finally, jealousy emerges as an emotional event (jealous flash) in response to a more or less significant change in the behavior of the partner, and reveals to the jealous individual a dimension which was previously latent or inexistent. This intense and brief experience, leaves a more or less blurred memory behind, and tends to progressively repeat itself and take root as a feeling.